IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA PENINGKATAN MUTU PEMBELAJARAN MATA PELAJARAN AQIDAH AKHLAQ DI MTS DARUL FATTAH TAHUN PELAJARAN 2023/2024 - Herwansyah (UNISAN JURNAL, 2024)
During this time, educators tend to pay attention to the class as a whole, not individuals or groups, so that individual differences receive less attention. Another symptom can be seen from educators using strategies and learning methods that are not optimal. Learning that does not pay attention to individual differences in children is based on the wishes of educators, it will be difficult to lead students towards achieving learning goals. Problems found in the classroom in the learning process include students who are slow to learn, low learning achievement, dependent, less responsive and less active. On the basis of the problems above, the problem formulation that the author proposes in this research is: Why Implement Active Learning Strategies in Improving the Performance of Aqidah Akhlak Teachers at MTS Darul Fattah. Objective: to find out why the implementation of active learning strategies has not been able to improve student learning achievement at MTS Darul Fattah. This research is descriptive qualitative field research or evaluates how the implementation of active learning management improves student learning achievement. In this research, the data collection methods used were observation, interviews and documentation. The data obtained is then processed using steps for data reduction, display, verification and drawing conclusions. The results of this research show that student learning achievement has not improved in a better direction due to the following factors: (1) Teachers’ attention to inactive students is still lacking, (2) Teachers do not understand the true potential of students, often measuring students’ abilities. using standards that exceed reality, so that it gives the impression that students must be able, (3) Less optimal use of media that supports learning activities, (4) Teachers still dominate teaching and learning activities, (5) The language used by teachers is less communicative, (6) Explanations regarding evaluation guidelines, especially activities that students must carry out, is lacking. Active learning strategies if implemented optimally will get a good response from students. This is shown by the increase in student responses in each meeting.